Women’s Changing Opportunities and Aspirations Amid Male Outmigration: Insights from Makueni County, Kenya - Crossland, M.; Paez Valencia, Ana Maria; Pagella, Tim; Mausch, K.; Harris, D.; Dilley, L.; Winowiecki, Leigh Ann (Springer, 2021)
In Makueni County, Kenya, an area experiencing intensifying migration flows, we investigate the aspired futures of rural men and women using a novel methodology combining a narrative-based survey tool, focus group discussions and semi-structured interviews. Our findings indicate that, in the absence of men and presence of norms restricting women's movement out of rural life, women are becoming increasingly engaged in farm management. Women’s aspirational narratives focused on commercialising farm activities, likely reflecting their changing agricultural opportunity space and new realities as farm managers. We highlight that only considering aspirations at the household level overlooks differing individual contributions, agency over various household income streams and individuals’ changing roles throughout life. Based on our findings, we make recommendations for further aspirations research including explicit consideration of intrahousehold heterogeneity and how individual strategies and aspirations interrelate and are negotiated at the household level to build an overall livelihood strategy.